Pendampingan Naposo Nauli Bulung Dalam Penguatan Pendidikan Akidah Dan Akhlak Remaja Di Desa Aek Haruaya Kecamatan Portibi Kabupaten Padang Lawas Utara - Nurhaliza Dalimunthe; Solihah Titin Sumanti; Ihsan Satrya Azhar (PT. Pustaka Cendekia Publisher, 2024)
Abstract. This study aims to find out the mentoring process carried out by Naposo Nauli Bulung in strengthening adolescent faith and moral education in Aek Haruaya Village, Portibi District, North Padang Lawas Regency. This research uses a qualitative method with a phenomenological approach, data is collected through observation, interviews, and documentation. The results of the study show that; 1) The assistance provided by Naposo Nauli Bulung as a whole has a positive impact on the community, especially adolescents, through various religious and social activities. Teenagers are guided to become individuals with noble character, knowledge, and responsibility. 2) The form of assistance includes the recitation of wirit yasin, lecture studies, fardu kifayah training, cleaning mosques and TPU, as well as Islamic holiday celebrations. 3) The obstacles faced include lack of facilities and human resources, lack of community or parental support, the influence of modern lifestyles, and lack of training for the community in organizing programs.